Deep cerebral microbleeds are associated with the severity of lacunar infarcts and hypertension: A retrospective analysis. Issue 23 (June 2018) - Gao, Zhongbao; Zhai, Yongzhi; Zhao, Xingli; Wang, Wei; Wu, Weiping; Wang, Zhenfu; Liu, Ruozhuo; Wang, Xiaodan
Abstract : Abstract: Cerebral microbleeds (CMBs) and lacunar infarcts are common manifestations of cerebral small vessel disease. However, the association between the location of CMBs and lacunar infarcts is unclear. Our study aimed to clarify the relationship between the location of CMBs and lacunar infarcts. This study retrospectively analyzed 166 patients with ischemic stroke or transient ischemic attacks admitted in the Geriatric Neurology Department of Chinese PLA General Hospital between February 2010 and December 2012. We collected clinical characteristics and risk factors of CMBs. The location of CMBs on T2*-weighted angiography was assessed by the Microbleed Anatomical Rating Scale. The number of lacunar infarcts and the severity of white matter hyperintensities were also recorded. The association between the location of CMBs and lacunar infarcts parameters was examined. CMBs were present in 77 (46.4%) patients. The presence [odds ratios (OR), 2.14; 95% confidence interval (CI), 1.02–4.48], number (OR, 1.17; 95% CI, 1.02–1.36 per lesion), severity (OR, 1.61; 95% CI, 1.07–2.42) of lacunar infarcts, and hypertension (OR, 5.76; 95% CI, 2.01–16.55) were independent risk factors for CMBs. Stratified by the location of CMBs, lobar CMBs and infratentorial CMBs did not show significant association with lacunar infarcts. Deep CMBs were significantly associated with the number (OR 1.18, 95% CI 1.03–1.36) and severity (OR 1.71, 95% CI 1.11–2.63) of lacunar infarcts. Moreover, the percentage of deep CMBs increased with the increased severity of lacunar infarcts ( P  = .003). Deep CMBs rather than lobar and infratentorial CMBs are associated with lacunar infarcts.